Prognostic Value of Body Composition in Therapy-Naive Patients with Non-Small Cell Lung Cancer - KIRATLI YOLCU, TUĞBA; KESİM, SELİN; FİLİZOĞLU, NUH; ÖNEŞ, TUNÇ; YUMUK, PERRAN FULDEN (My University, 2024)
The objective of this study was to assess the impact of visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), skeletal muscle mass volume (SMMV), and VAT/SAT ratio on the prognosis of therapy naive metastatic non-small cell lung cancer (NSCLC) patients undergoing different therapy regimens. Eighty three patients with stage-IV NSCLC who were received at least one cycle of platinum-based chemotherapy (PBCT) or tyrosine kinase inhibitor (TKI) therapy included in this retrospective study. Pre-treatment multi-slice and single-slice computed tomography images of PET/CT scans were used for the assessment of body composition. The effect of anthropometric measurements on clinical outcomes for advanced NSCLC patients was investigated with survival analysis for each treatment subgroup. In univariate analyses, female gender (p= 0.03), presence of bone metastasis (p= 0.02), presence of adrenal metastasis (p< 0.005), SAT volume (p= 0.01), VAT/SAT ratio (p= 0.02) and serum albumin levels (p= 0.01) were found to be statistically significant for overall survival (OS) in TKI treatment group. In multivariate analyses, only serum albumin level (p< 0.005) remained an independent risk factor. No significant results were found in the PBCT treatment group. Single-slice volume calculation method for VAT measurement was highly correlated with a multi-slice method which reflects the entire abdominopelvic region. In conclusion, our study indicates that adipose tissue and muscle mass volume alone do not significantly affect survival in patients with metastatic NSCLC. However, hypoalbuminemia was identified as an independent negative prognostic factor.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY; ONCOLOGY; Body composition; Multi-slice computed tomography; Non-small cell lung cancer; Subcutaneous adipose tissue; Visceral adipose tissue